Therapeutic Potential of Lipid Nanoparticle‐Encapsulated CD19‐Targeting mRNAs in Lupus and Rheumatoid Arthritis - Chipeng Guo; Yingsen Tang; Ling Zeng; Xiaomei You; Siweier Luo; Yufei Du; Le Wang; Liangchun Wang; Jianchuan Wang; Jinjin Chen; Yiming Zhou (Advanced Science)
Abstract The hyperactivation of autoreactive B cells and plasma cells leads to the development of systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), therefore, targeting the abnormal B cells and plasma cells might hold promise for the treatment of these refractory and relapsing diseases. This study developed lipid nanoparticle‐encapsulated mRNA‐encoding antibodies (mRNab‐LNPs) targeting CD19, and evaluated their therapeutic efficacy in lupus and RA mice. mRNab‐LNPs enabled robust production of anti‐CD19 antibodies in multiple cell lines in vitro. Interestingly, intramuscular injection of mRNab‐LNPs resulted in high and sustained production of anti‐CD19 antibodies in mice. In particular, the numbers of CD19+ circulating B cells and tissue‐resident plasma cells are significantly reduced by mRNab‐LNPs in mice. As a result, mRNab‐LNPs significantly reduced the histopathological changes and tissue injuries in both lupus and RA mice. Collectively, these findings demonstrate the therapeutic and translational potential of mRNab‐LNPs in the treatment of SLE and RA.